Further heterogeneity in Silver–Russell syndrome: PLAG1 deletion in association with a complex chromosomal rearrangement. Issue 10 (5th July 2021) - Brereton, Rebecca E.; Nickerson, Sarah L.; Woodward, Karen J.; Edwards, Tracey; Sivamoorthy, Soruba; Ramos Vasques Walters, Fabiana; Chabros, Vicki; Marchin, Vanessa; Grumball, Tanya; Kennedy, Dagmara; Uzaraga, Joan; Peverall, Joanne; et al.
Abstract: Silver–Russell syndrome (SRS) is a rare genetic condition primarily characterized by growth restriction and facial dysmorphisms. While hypomethylation of H19/IGF2 :IG‐DMR (imprinting control region 1 [IC1]) located at 11p15.5 and maternal uniparental disomy of chromosome 7 (upd[7]mat) are the most common genetic mechanisms responsible for SRS, the expanding body of literature describing alternative causative variants suggests SRS is a highly heterogeneous condition, also involving variation in the HMGA2‐PLAG1‐IGF2 pathway. We report a familial PLAG1 deletion in association with a complex chromosomal rearrangement. We describe two siblings with differing unbalanced chromosomal rearrangements inherited from a mother with a 5‐breakpoint balanced complex rearrangement involving chromosomes 2, 8, and 21. The overlapping but diverse phenotypes in the siblings were characterized by shared SRS‐like features, underlined by a PLAG1 whole gene deletion. Genetic analysis and interpretation was further complicated by a meiotic recombination event occurring in one of the siblings. This family adds to the limited literature available on PLAG1 ‐related SRS. We have reviewed all currently known cases aiming to define the associated phenotype and guide future genetic testing strategies. The heterogeneity of SRS is further expanded by the involvement of complex cytogenomic abnormalities, imposing requirements for a comprehensive approach to testing and genetic counseling.